2, 4-Dichloro-6-nitrophenol, a photonitration product of 2, 4-dichlorophenol, caused anti-androgenic potency in Chinese rare minnows (Gobiocypris rarus). (September 2016) - Chen, Rui; Liu, Cao; Yuan, Lilai; Zha, Jinmiao; Wang, Zijian
Abstract: 2, 4-Dichloro-6-nitrophenol (DCNP) is an environmental transformation product of 2, 4-dichlorophenol that has been identified as widespread in effluent wastewater, but little is known about its toxicity because this compound is not regulated. Therefore, to investigate the endocrine disruption potency of DCNP in Chinese rare minnows ( Gobiocypris rarus ), adult and juvenile fish were exposed to various concentrations of DCNP (2, 20, and 200 μg/L) for 28 d. After 28 d exposure, the plasma vitellogenin (VTG) levels were reduced in females while increased in males and juvenile fish considerably, as compared with the control. These results suggested that DCNP affects the HPG-axis in a sex-dependent way. Testosterone (T) levels in the plasma were significantly lower in adult and juvenile fish and were accompanied by an increased estradiol (E2)/T ratio. Histopathological observation revealed hypertrophy of the hepatocytes and nuclear pyknosis in the liver, the inhibition of spermatogenesis in the testes, and the degeneration of oocytes in the ovaries after DCNP exposure. The expression pattern of selected genes indicated that the nuclear receptor, steroidogenesis and gonadotropin regulation pathways were perturbed after DCNP exposure. Above all, our results demonstrated that DCNP clearly had anti-androgenic activity in both adult and juvenile fish and can therefore be considered as an endocrine-disrupting chemical. Graphical abstract: Highlights: An environmental transformation product induced anti-androgenic effects. DCNP induced gender-specific responses in fish hormone levels. DCNP led to morphological changes in the liver and the gonads. The HPG-axis related pathways were perturbed after DCNP exposure. Abstract : 2, 4-Dichloro-6-nitrophenol exposure affected the pathology, plasma VTG and steroid levels and gene transcription in the HPG-axis in Chinese rare minnows.